The Deepfake Phenomenon as a New Form of Cybercrime from a Criminological Perspective - Rahayu, Anisa; Kuswandi (Indonesian Journal Publisher, 2025)
This study seeks to dissect the operational patterns of cybercrimes that leverage deepfake technology, with a specific focus on fraud schemes that digitally superimpose the likeness of public figures onto deceptive content. Through a criminological lens, it explores the psychological and social drivers behind such acts, the multifaceted harms inflicted on victims and society, and the significant hurdles faced by Indonesian law enforcement in responding to these technologically advanced offenses. Employing a descriptive-analytical methodology, the research synthesizes case studies, legal document analysis, and theoretical frameworks to map the crime's ecosystem. The analysis uncovers a triad of enabling factors: a deficit in societal oversight that fails to curb digital misconduct, a social learning environment where deviant online behavior is acquired and normalized, and a critical regulatory vacuum that lacks laws specifically tailored to govern synthetic media. Presently, authorities are forced to apply existing statutes namely the Criminal Code (KUHP) and the Electronic Information and Transactions (ITE) Law which are often ill suited to tackle the evidentiary and jurisdictional intricacies of deepfake fraud. Consequently, this research argues for a decisive, multi-layered counter-strategy. It underscores the imperative to elevate public digital literacy, empowering citizens to critically evaluate media. It calls for the drafting of agile, forward-looking regulations that directly address content provenance and accountability. Finally, it highlights the necessity of investing in advanced detection tools capable of identifying sophisticated forgeries in real-time, thereby forming a crucial bulwark against this evolving threat to digital trust and security.